1989
DOI: 10.1029/jb094ib10p14099
|View full text |Cite
|
Sign up to set email alerts
|

Conductive structures and tectonics beneath the EMSLAB land array

Abstract: Magnetovariation fields were recorded by the land part of the EMSLAB array, August‐September 1985. Data from two complete days and two shorter sequences, chosen for moderate magnetic activity, are here used to map induced currents, which flow preferentially in the more conductive rocks, in Washington and Oregon and adjoining areas. Fourier transform anomaly maps, induction vectors, and hypothetical event anomaly maps are used to delineate conductive structures. These include the ocean and suboceanic asthenosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…A large onshore-offshore magnetotelluric experiment, EMSLAB, completed in the late 1980s, is an example of the focus given to Cascadia Gough et al, 1989;Wannamaker et al, 1989;Jiracek et al, 1989;Hellfrich, 2003). At the time it was completed, it was the largest and most ambitious experiment of its kind, and was a consortium effort of 12 institutions in four countries ).…”
Section: Emslab Experimentsmentioning
confidence: 97%
See 1 more Smart Citation
“…A large onshore-offshore magnetotelluric experiment, EMSLAB, completed in the late 1980s, is an example of the focus given to Cascadia Gough et al, 1989;Wannamaker et al, 1989;Jiracek et al, 1989;Hellfrich, 2003). At the time it was completed, it was the largest and most ambitious experiment of its kind, and was a consortium effort of 12 institutions in four countries ).…”
Section: Emslab Experimentsmentioning
confidence: 97%
“…A regional magnetovariational (MV) study, which uses the time-varying magnetic field alone to infer structure, identified several distinct tectonic regimes including the northwestern Basin and Range and segmentation of the volcanic chain near Mt St. Helens and Mt Adams. The MV data also demonstrated a fundamentally N-S preferred orientation to structure over most of the survey domain (Gough et al, 1989). A detailed central transect of MT soundings, the Lincoln Line, incorporated both seafloor and land stations with data to periods of 10,000 s over a length of nearly 700 km.…”
Section: Emslab Experimentsmentioning
confidence: 98%
“…One example is the EMSLAB array (Gough et al 1989). Some decades ago, various large 1-D or bi-dimensional (2-D) arrays of magnetometers were deployed around the world to study both the electrical structure of the crust and upper mantle and the morphology of the external magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…6 does not support the presence of an elongated conductor, although a very localized one around one station in Alberta is apparent. The EMSLAB array maps (GOUGH et al, 1989) are equivocal on this question, although GOUGH et al (1989) consider that they support the existence of the SABC conductor. They do, however, express surprise that "the (SABC) currents stopped at the border".…”
Section: Previous Em Studies In the Regionmentioning
confidence: 99%